If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(x-2)+5=3-6(3-x)
We move all terms to the left:
4(x-2)+5-(3-6(3-x))=0
We add all the numbers together, and all the variables
4(x-2)-(3-6(-1x+3))+5=0
We multiply parentheses
4x-(3-6(-1x+3))-8+5=0
We calculate terms in parentheses: -(3-6(-1x+3)), so:We add all the numbers together, and all the variables
3-6(-1x+3)
determiningTheFunctionDomain -6(-1x+3)+3
We multiply parentheses
6x-18+3
We add all the numbers together, and all the variables
6x-15
Back to the equation:
-(6x-15)
4x-(6x-15)-3=0
We get rid of parentheses
4x-6x+15-3=0
We add all the numbers together, and all the variables
-2x+12=0
We move all terms containing x to the left, all other terms to the right
-2x=-12
x=-12/-2
x=+6
| -20=4-7x-x | | 5=z/11+7 | | 24x^2+19x=2 | | 2r=3r+7 | | 2x(x2-2)+7x=9x+2x3 | | 1+0,25y+10*0,4=0 | | -3-9g=2g+8 | | a/4+5=15 | | 4(v-9)-8=-6(-3v+6)-8v | | -75=8w+5 | | 15y-48+63=180 | | 5x-9+38=74 | | -3d=10-2d | | 133=11y-32 | | 2x-5/2=9/4 | | u· 78= 14 | | -8j=4-7j | | 4(x+3)-7=x+3(x+1) | | 3v-16=29 | | 3r+5+5=7 | | 6u=14-u | | 49n=14 | | x-(x*0.07)=412,596.26 | | X(5+x)=x2+3x+1 | | -x+41=2x+17 | | 5b+4=3b−4 | | -7m+8=-6m | | 9-z/2=14 | | 6p=516 | | -5y=-4-y8 | | 722=t+650 | | 22u=616 |